2018
DOI: 10.1371/journal.pone.0199865
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and arterial hypertension—Data from Sephar III survey

Abstract: ObjectivesThis paper aims to evaluate the association between serum uric acid (SUA) levels, arterial hypertension (HT) prevalence, blood pressure values control, kidney function and intima media thickness (IMT), as a surrogate marker of early atherosclerosis, in a representative group of Romanian adult population.Materials and methodsThe study sample consists in 1920 adults included in SEPHAR III (Study for the Evaluation of Prevalence of Hypertension and cArdiovascular Risk in Romania) survey (mean age 48.63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 11 publications
2
19
0
3
Order By: Relevance
“…[6] The SUA concentration in adult women, which were lower than in men of a similar age, it could be related to a higher renal clearance of uric acid in women, possibly due to higher oestrogen levels in their plasma. [10] In this study significant relation was observed between uric acid and hypertension this results was consistent with a study conducted with 297 individuals from Cameroon population, [11] in study with 163 individuals more than 70 years of age admitted in hospital due to a first time ever acute ischemic/ non-embolic stroke and 166 volunteers without a history of cardiovascular disease in Greece, [6] study with 1920 adults from Romanian adult population, [12] and also a cohort study from china with 1082 healthy participants aged 41 to 70 years. [13] A meta-analysis and systematic review concluded that 1.0 mg/dl increase in SUA level is associated with an increased risk of incident hypertension by 13%.…”
Section: Discussionsupporting
confidence: 89%
“…[6] The SUA concentration in adult women, which were lower than in men of a similar age, it could be related to a higher renal clearance of uric acid in women, possibly due to higher oestrogen levels in their plasma. [10] In this study significant relation was observed between uric acid and hypertension this results was consistent with a study conducted with 297 individuals from Cameroon population, [11] in study with 163 individuals more than 70 years of age admitted in hospital due to a first time ever acute ischemic/ non-embolic stroke and 166 volunteers without a history of cardiovascular disease in Greece, [6] study with 1920 adults from Romanian adult population, [12] and also a cohort study from china with 1082 healthy participants aged 41 to 70 years. [13] A meta-analysis and systematic review concluded that 1.0 mg/dl increase in SUA level is associated with an increased risk of incident hypertension by 13%.…”
Section: Discussionsupporting
confidence: 89%
“…Higher values of SUA and body mass index have been associated with eGFR decline of 50% or end-stage kidney disease in patients with arterial/arteriolar nephrosclerosis [76]. Furthermore, increased SUA correlates with increased intima media thickness values as markers of atherosclerosis and suboptimal blood pressure control [77]. Contrarily, some researchers have shown that hyperuricemia and higher SUA were associated with lower risk of all-cause and CV mortality in the hemodialysis population [78,79].…”
Section: Hyperuricemia and Kidney Diseasementioning
confidence: 99%
“…Buzas R et al, reported that increased SUA levels are associated with arterial hypertension and with suboptimal BP control in treated hypertensive subjects. 16 In this study, 18 patients were obese BMI >25 (43%). These patients had elevated uric acid levels.…”
Section: The Tests Of Significance Didn't Find Any Correlation Betweementioning
confidence: 66%